Factors Associated With Benefit of Treatment of Patent Ductus Arteriosus in Preterm Infants: A Systematic Review and Meta-Analysis - Jansen, Esther J. S.; Hundscheid, Tim; Onland, Wes; Kooi, Elisabeth M. W.; Andriessen, Peter; de Boode, Willem P. (Frontiers in Pediatrics, 2021)
Context: There is an ongoing debate on the optimal management of patent ductus arteriosus (PDA) in preterm infants. Identifying subgroup of infants who would benefit from pharmacological treatment might help. Objective: To investigate the modulating effect of the differences in methodological quality, the rate of open-label treatment, and patient characteristics on relevant outcome measures in randomized controlled trials (RCTs). Data Sources: Electronic database search between 1950 and May 2020. Study Selection: RCTs that assessed pharmacological treatment compared to placebo/no treatment. Data Extraction: Data is extracted following the PRISMA guidelines. Outcome measures were failure to ductal closure, surgical ligation, incidence of necrotizing enterocolitis, bronchopulmonary dysplasia, sepsis, periventricular leukomalacia, intraventricular hemorrhage (IVH) grade ≥3, retinopathy of prematurity and mortality. Results: Forty-seven studies were eligible. The incidence of IVH grade ≥3 was lower in the treated infants compared to the placebo/no treatment (RR 0.77, 95% CI 0.64-0.94) and in the subgroups of infants with either a gestational age <28 weeks (RR 0.77, 95% CI 0.61-0.98), a birth weight <1000 g (RR 0.77, 95% CI 0.61-0.97), or if untargeted treatment with indomethacin was started <24 hours after birth (RR 0.70, 95% CI 0.54-0.90). Limitations: Statistical heterogeneity caused by missing data and variable definitions of outcome parameters. Conclusions: Although the quality of evidence is low, this meta-analysis suggests that pharmacological treatment of PDA reduces severe IVH in extremely preterm, extremely low birth weight infants or if treatment with indomethacin was started <24 hours after birth. No other beneficial effects of pharmacological treatment were found.